Comparison of Autistic Individuals Who Engage in Self-Injurious Behavior, Aggression, and Both Behaviors - Stephen M. Edelson (MDPI AG, 2021)
Background. Two of the most challenging behaviors exhibited by individuals on the autism spectrum are self-injurious behavior (SIB) and aggression. The aim of this study was to identify co-occurring symptoms, behaviors, and medical comorbidities that may provide insight into understanding and treating these behaviors. Method. A large-scale online survey was used to collect data on symptoms, behaviors, and medically related comorbidities commonly reported in individuals with autism spectrum disorders (ASD). Based on responses from 2327 participants, individuals with ASD were divided into four categories: individuals who engaged in SIB only, individuals who engaged in aggression only, individuals who engaged in both behaviors, and individuals who engaged in neither behavior. Results. There were several characteristics and comorbidities associated with those who engaged in SIB only and in aggression only, in addition to those who engaged in both behaviors. Conclusion. The findings in this study provide evidence to support at least two underlying causes of these behaviors (insensitivity to pain and reactions to food) as well as implications for treating them. Furthermore, several behaviors often observed during early childhood may be considered early predictors of these challenging behaviors.